Susac's Syndrome in a Patient Diagnosed with MS for 20 Years: A Case Report. (2nd February 2014) - Nazliel, Bijen; Akyol, Asli; Zeynep Batur Caglayan, Hale; Yildirim-Capraz, Irem; Irkec, Ceyla
Abstract : Susac's syndrome is an uncommon neurologic disorder of unknown cause. It has been described as a clinical triad of encephalopathy, hearing loss, and branch retinal artery occlusions. Clinically the diagnosis is difficult when the patient presents only a portion of a triad. We present a case with vision loss and sensorineural deafness and who had been diagnosed with MS for 20 years. Susac's syndrome is presumed to be an autoimmune endotheliopathy. Neurologic symptoms and signs are diffuse and multifocal, acute or subacute in onset, and progress during the active phase of the disease. In some patients the onset was stroke like and in others that of subacute dementia. Headache, often with migrainous features, was a prominent feature initially in more than one half of the patients. A high index of suspicion leading to correct diagnosis and early appropriate therapy may reduce the permanent sequel seen with this disease. Misdiagnosis is common. In patients in whom diagnosis and treatment are delayed permanent morbidity is higher in terms of visual loss, hearing loss, and neurologic debility. In patients in whom rapid diagnosis has led to early administration of immunosuppressive therapy, recovery can be almost complete.